2018
DOI: 10.1245/s10434-018-6431-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation is a Promising Therapy for Pancreatic Ductal Adenocarcinoma in Conjunction with Current Chemoradiation Therapy

Abstract: In conjunction with established current therapies, vitamin D supplementation may be an effective treatment for PDAC patients by inactivating CAFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The beneficial effects of vitamin D supplementation on the survival of PDAC patients have been attributed not only to its direct anticancer effects [13], but also to its effects on the tumor microenvironment. In patients undergoing pre-operative chemoradiotherapy, Mukai et al demonstrated that distant metastases-free survival was longer in those with higher than in those with lower levels of vitamin D, which, according to the authors, acts by suppressing the activation of CAFs [14]. In agreement, Sherman et al demonstrated that vitamin D receptor engagement acts as a master transcriptional regulator of PSCs and, in association with standard gemcitabine treatment, prolongs survival in genetically engineered mice [15].…”
Section: Introductionmentioning
confidence: 90%
“…The beneficial effects of vitamin D supplementation on the survival of PDAC patients have been attributed not only to its direct anticancer effects [13], but also to its effects on the tumor microenvironment. In patients undergoing pre-operative chemoradiotherapy, Mukai et al demonstrated that distant metastases-free survival was longer in those with higher than in those with lower levels of vitamin D, which, according to the authors, acts by suppressing the activation of CAFs [14]. In agreement, Sherman et al demonstrated that vitamin D receptor engagement acts as a master transcriptional regulator of PSCs and, in association with standard gemcitabine treatment, prolongs survival in genetically engineered mice [15].…”
Section: Introductionmentioning
confidence: 90%
“…In addition, the relationship among VD, VD receptor (VDR) and prognosis of PDAC were reported. Investigators demonstrated that low expression of VDR or low circulating VD level (<20 ng/ml) was related to a poor prognosis of PDAC ( 185 187 ). Gene expression profiling studies demonstrated that PSCs showed a strong expression of VDR ( 137 ).…”
Section: Current Progress In Targeting Strategiesmentioning
confidence: 99%
“…Higher levels of blood 25-hydroxyvitamin D [25(OH)D] are associated with longer survival duration in patients with PC [ 14 ]. Experimental evidence indicates that vitamin D exerts anticancer effects by inhibiting cancer cell proliferation, inducing apoptosis and differentiation and potentiating chemo- or radiotherapy in various cancers [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Interestingly, experimental data also demonstrate that vitamin D regulates the tumor microenvironment, particularly cancer-associated fibroblast reprogramming, to facilitate tumor repression [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%